Analisis Tingkat Pemahaman Konsep Mahasiswa Terhadap Matakuliah Aplikasi Komputer Bisnis - Aswidani, Aswidani (Green Publisher Indonesia, 2025)
This research aims to determine the level of students' understanding of the concept of the Business Computer Application (Aplikombis) course; -In studying the Applicombis course, it is hoped that students have an understanding of concepts related to computer systems, so that students can easily and quickly take the course. The research was conducted on students in the second semester of the management study program in 2020/2021 which was divided into 4 classes; class II A, class II B, class II C and class II D This study uses a quantitative descriptive approach and test instruments; There are 39 question items divided into 8 hardware questions, 11 software system questions, 14 application software questions and 6 brainware question items. The results of the study show that the percentage of concept understanding level of students in the second semester of the 2020/2021 management study program towards the business computer application course is 62%, with details of 75% of students being able to repeat the concepts studied, 57% being able to clarify objects based on concepts, 50% being able to make examples and not examples, and 68% being able to relate concepts to other concepts. The level of understanding of the concept of class A students towards the application course is 71%, (high), the level of understanding of the concept of class B students is 54% (moderate), the level of understanding of the concept of class C students is 59% (moderate) and the level of understanding of the concept of class D students is 55% (moderate). The average student has a